2017
DOI: 10.1038/srep42045
|View full text |Cite
|
Sign up to set email alerts
|

The Demographic Features, Clinicopathological Characteristics and Cancer-specific Outcomes for Patients with Microinvasive Breast Cancer: A SEER Database Analysis

Abstract: To investigate the clinicopathological characteristics and survival outcomes of microinvasive breast cancer, we conducted an observational study of female diagnosed with DCIS or DCIS with microinvasion (DCISM) from 1990 to 2012 using the Surveillance, Epidemiology, and End Results (SEER) database. There were 87695 DCIS and 8863 DCISM identified. In DCISM group, patients appeared to be younger and more black patients were identified in comparison with DCIS group. Furthermore, DCISM was associated with more aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
31
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 43 publications
10
31
3
Order By: Relevance
“…[2830] Our results confirmed previous studies that showed a reduced OS in DCISM than DCIS. [28,29] In addition, several studies suggested that DCISM survival outcomes were intermediate between DCIS and IDC, while in our study we found it to be very similar to IDC, mainly because of distant metastases occurrence. [30,31]…”
Section: Discussionsupporting
confidence: 49%
“…[2830] Our results confirmed previous studies that showed a reduced OS in DCISM than DCIS. [28,29] In addition, several studies suggested that DCISM survival outcomes were intermediate between DCIS and IDC, while in our study we found it to be very similar to IDC, mainly because of distant metastases occurrence. [30,31]…”
Section: Discussionsupporting
confidence: 49%
“…A number of relevant studies have investigated the histopathological characteristics and clinical outcomes of microinvasive DCIS; how patient survival and the biological behaviour of this rare form of breast carcinoma differ from DCIS remain controversial. Microinvasive DCIS is frequently found in a high nuclear grade comedo DCIS setting, and less frequently with other types of DCIS or lobular carcinoma in situ .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the positive rates of ER and PR were lower than those reported in the literature, while the positive rates of HER2 were higher than those reported in the literature, which may be related to race, or the proportion of high-grade DCIS in this study was higher. 17 In this study, there was no difference in hormone status between the 2 forms of MI.…”
Section: Discussionmentioning
confidence: 45%